Determinan Kepatuhan Wajib Pajak Kendaraan Bermotor Studi Pada Pemerintahan Kabupaten/Kota di Provinsi Jambi - Nazmi, Fadilah (Brida Provinsi Jambi, 2024)
Abstract This research aims to understand the socio-economic characteristics of motor vehicle taxpayers (PKB) in Jambi Province and analyze the influence of education level, type of work, and income level on PKB taxpayer compliance. This research uses primary data collected from 141 respondents in 11 districts/cities in Jambi Province during the 2018-2022 period. Data analysis was carried out using logistic regression. The results of the research show that the level of education has a negative influence, this is because the level of education for some people, especially those with high education and just starting their careers, can influence the cost of Motor Vehicle Tax (PKB). be a significant financial burden, while the type of work has a positive effect. This is because taxpayers with stable and secure employment have a more stable income, this also allows them to more easily allocate funds to pay motor vehicle taxes and this income level has a positive effect. This is because taxpayers with high levels of income generally have greater financial capacity to fulfill their obligations to pay motor vehicle tax, thereby minimizing the potential for delays or arrears in tax payments. Keywords: Education level, type of work, income level